(untitled) (Journal of the College of Basic Education, 2022)
Some people have always thought that Runner’s theology is a moderate theology. On the one hand, he tried to re-read the traditional tradition, and on the other hand, he tries, through reading and interpreting the traditional tradition, to answer modern challenges and questions. In other words, Rahner tried to find a balance between the theory of the philosophy of transcendence, which is the traditional Catholic theology, which emphasizes the gap between the world of theology and the world of humanity on the one hand, and natural philosophy (immanence), which is modernity, which is in line with the theology of our world. Hence, we find that Hans Frey added Runner’s theology to his divisions of Christian theology. He placed liberal theology and conservative theology at the beginning and at the end of his theological divisions, and inserted three theologies between them, including Runner’s theology. We also find that David Ford, when discussing the theology of Hans Frey, made Rahner’s theology a sixth section in addition to the five sections that Hans Frey referred to. One of the most important components of Rahner’s theology is the philosophical knowledge of man and Rahner’s holistic salvation, which we aim to discuss in this article.